A population-based study of treated mental health and persistent pain conditions after transport injury. Issue 10 (October 2018) - Giummarra, Melita J.; Black, Oliver; Smith, Peter; Collie, Alex; Hassani-Mahmooei, Behrooz; Arnold, Carolyn A.; Gong, Jennifer; Gabbe, Belinda J.
Abstract: Background: Persistent pain and mental health conditions often co-occur after injury, cause enormous disability, reduce social and economic participation, and increase long-term healthcare costs. This study aimed to characterise the incidence, profile and healthcare cost implications for people who have a treated mental health condition, persistent pain, or both conditions, after compensable transport injury. Methods: The study comprised a population cohort of people who sustained a transport injury (n = 74, 217) between 2008 to 2013 and had an accepted claim in the no-fault transport compensation system in Victoria, Australia. Data included demographic and injury characteristics, and payments for treatment and income replacement from the Compensation Research Database. Treated conditions were identified from 3 to 24-months postinjury using payment-based criteria developed with clinical and compensation system experts. Criteria included medications for pain, anxiety, depression or psychosis, and services from physiotherapists, psychologists, psychiatrists, and pain specialists. The data were analysed with Cox Proportional Hazards regression to examine rates of treated conditions, and general linear regression to estimate 24 month healthcare costs. Results: Overall, the incidence of treated mental health conditions ( n  = 2459, 3.3%) and persistent pain ( n  = 4708, 6.3%) was low, but rates were higher in those who were female, middle aged (35–64 years), living in metropolitan areas or neighbourhoods with high socioeconomic disadvantage, and for people who had a more severe injury. Healthcare costs totalled more than $A707 M, and people with one or both conditions (7.7%) had healthcare costs up to 7-fold higher (adjusting for demographic and injury characteristics) in the first 24 months postinjury than those with neither condition. Conclusions: The incidence of treated mental health and persistent pain conditions was low, but the total healthcare costs for people with treated conditions were markedly higher than for people without either treated condition. While linkage with other public records of treatment was not possible, the true incidence of treated conditions is likely to be even higher than that found in this study. The present findings can be used to prioritise the implementation of timely access to treatment to prevent or attenuate the severity of pain and mental health conditions after transport injury.